PATTERN OF CRANIO – INTRACRANIAL INJURIES IN DEATH DUE TO FATAL VEHICULAR ACCIDENTS IN A COSMOPOLITAN CITY - Rautji, Ravi; Kumar , Avishek; Harish, S (Journal of Forensic Medicine and Toxicology, 2012)
Head injury is an important cause of mortality worldwide. Head is most vulnerable part of the body involved in road traffic accidents. The present study was undertaken on 112 victims of road traffic accidents who died due to head injuries. Males accounted for 100 (89.3%) cases as compared to females 12 (10.7%). Most of the accidents occurred between 3 PM to 6 PM comprising 23.2% of total cases. The peak incidence was observed in the age group of 21-30 years comprising 33 % of the cases. Skull fracture was seen in 99 (88.4%) cases. The combination of vault and skull base fracture was the commonest (n = 53, 47.3%). The commonest type of skull fracture was comminuted fracture (n = 58, 58.5%) followed by fissured fracture (n = 34, 34.3 %). Among the intracranial hemorrhages combination of subdural and subarachnoid hemorrhage was the commonest (n = 55, 49.1%).
Keywords: Road Traffic accident; Fracture; Cranio cerebral; Intracranial Haemorrhage; pedestrian